TRADISI MAKAN SIRIH PINANG SEBAGAI MODEL MODERASI BERAGAMA BERBASIS KEARIFAN LOKAL DI KELURAHAN NIKI-NIKI, KABUPATEN TIMOR TENGAH SELATAN – NTT - Henderikus Nayuf (Harmoni, 2022)
This paper explains the value and meaning of the tradition of eating betel - areca nut as a model of local wisdom-based religious moderation in Niki-Niki Village. by describing the value and meaning of the tradition including the challenges and opportunities for developing it. The research method is qualitative using an ethnographic approach that is descriptive qualitative with flow analysis through data reduction, presentation and writing of conclusions and verification. The results of the study show that the tradition of eating betel - areca nut is a legacy of Atoni Pah Meto's local wisdom which binds brotherhood, embraces others and respects differences. Bonding, embracing and appreciating humanity are actualized through two models of religious moderation based on the tradition of betel nut eating, namely hospitality and solidarity. Thus it can be concluded that through the tradition of eating betel - areca nut, religious moderation can be actualized to the local community. This means that religious moderation is not only understood, interpreted and lived by certain circles, but is able to reach the grassroots community, specifically the Atoni Pah Meto tribe in Niki-niki Village.